2016
DOI: 10.1038/ijo.2016.126
|View full text |Cite
|
Sign up to set email alerts
|

Brain regions implicated in inhibitory control and appetite regulation are activated in response to food portion size and energy density in children

Abstract: This is the first fMRI study to report increased activation to large portions in a brain region that is involved in inhibitory control. These findings may contribute to understanding why some children overeat when presented with large portions of palatable food.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 58 publications
0
22
0
Order By: Relevance
“…7 Conceptually, eating in the absence of hunger is based on Schachter's externality theory of obesity 14 Consistent with the externality theory of obesity, a growing body of literature has shown differential sensory processing in the brain for hedonic taste and visual stimuli in youth with and without obesity. 18,25,27 Together, these data suggest that hedonically motivated disinhibited eating behaviour may be a manifestation of disrupted response to food cues within these brain regions. 19,25,26 Additionally, functional dysregulation of brain regions involved with cognitive and attentional control processes, specifically inhibitory control, is also implicated in hedonically motivated disinhibited eating behaviours.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…7 Conceptually, eating in the absence of hunger is based on Schachter's externality theory of obesity 14 Consistent with the externality theory of obesity, a growing body of literature has shown differential sensory processing in the brain for hedonic taste and visual stimuli in youth with and without obesity. 18,25,27 Together, these data suggest that hedonically motivated disinhibited eating behaviour may be a manifestation of disrupted response to food cues within these brain regions. 19,25,26 Additionally, functional dysregulation of brain regions involved with cognitive and attentional control processes, specifically inhibitory control, is also implicated in hedonically motivated disinhibited eating behaviours.…”
mentioning
confidence: 82%
“…[3][4][5][6][7][8][9][10][11][12] Hedonically motivated disinhibited eating behaviour, such as eating in the absence of hunger, is of particular concern given the ubiquitous availability of highly palatable, hedonic foods in modern society. [15][16][17][18][19] Specifically, brain regions subserving sensory processing and salience valuation of stimuli such as the insula, [20][21][22] and reward circuitry including the ventral striatum, amygdala, and ventral tegmental area, 23,24 are altered in hedonically motivated disinhibited eating behaviours. 7 Conceptually, eating in the absence of hunger is based on Schachter's externality theory of obesity 14 Consistent with the externality theory of obesity, a growing body of literature has shown differential sensory processing in the brain for hedonic taste and visual stimuli in youth with and without obesity.…”
mentioning
confidence: 99%
“…This region is important for semantic selection (44) and behavioral control of emotion and motivation (45,46). We previously reported increased activation to large-portion cues (31) in the IFG that were from BA 44, which is in proximity to a region that has been implicated in the taste response to cues (47) and is posterior to BA 47. We speculate that differences between results from that analysis and the current study may have been due to the different locations and functions within the IFG.…”
Section: Discussionmentioning
confidence: 99%
“…We previously tested a limited number of a priori-defined brain regions that have been implicated in reward processing and decision making in this same cohort with the use of a different analytic approach (31). However, there may be other brain regions that have not been previously tested that are responsive to food PS and ED cues.…”
Section: Methodsmentioning
confidence: 99%
“…Functional magnetic resonance imaging studies have shown positive correlations between viewing palatable food stimuli and blood-oxygen-leveldependent (BOLD) response in regions implicated in reward and inhibitory control (10)(11)(12). Alterations in these responses have been positively linked to weight gain (13,14) and obesity in adults (15)(16)(17) and children (18,19).…”
Section: Introductionmentioning
confidence: 99%